ORGANIZATIONAL AND LEGAL PRINCIPLES OF INVESTIGATION OF AVIATION DISASTERS - Сопілко, Ірина Миколаївна; Беззубов, Дмитро Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Objective: to determine the legal models for aviation accident investigation. To propose effective mechanisms of observing the rights and freedoms of a citizen and the interests of the state and legal entities in the investigation of aviation disasters. To offer author’s models of organizational support for the investigation of aviation disasters. Methods: the study was conducted using classical methods of scientific knowledge. With the help of the analysis method, the system elements of the legal mechanism for ensuring the rule of law in the investigation of aviation disasters are disclosed. With the help of the method of synthesis, variants of occurrence of situations of threats and dangers of a civilian aircraft during the flight task are considered. Results: according to the results of the study, mechanisms for effective law enforcement of aviation accident investigation were proposed. Identified and disclosed components of organizational support for the process of investigation of aviation disasters.